Disaster Prep: Development of Virtual Reality Application For Natural Disaster Preparedness And Response - Hairizan, Muhammad Hadzilhareeq; Murli, Dr. Norhanifah (Applied Information Technology And Computer Science, 2026)
Natural disasters such as floods, fires, and storms continue to pose serious threats to safety and infrastructure. In Malaysia, changing weather patterns have increased the frequency of such events, often catching unprepared residents off guard. This project introduces Disaster Prep, a virtual reality (VR) application designed to educate users on disaster preparedness through immersive simulation. Developed using Unity and based on the TRES-D methodology, the application features four modules: Ready-To-Go (RTG) bag preparation, fire response, flood response and storm sheltering. The target users are the general public aged 12 and above. Input from a Malaysian Civil Defense Force expert was incorporated to ensure realism and accuracy. Functional and user acceptance testing were conducted, with the System Usability Scale (SUS) producing an average score of 71.75, placing it in the "acceptable" range with a "Good" rating. The results show that Disaster Prep effectively supports disaster education by delivering engaging, realistic scenarios that increase awareness and preparedness. By offering interactive training in a safe virtual environment, the app aims to improve users’ decision-making and readiness during emergencies besides offering a scalable and modern solution for public safety training.